Study of the Effects of the COVID-19 Pandemic on Air Quality: A Case Study in Cluj-Napoca, Romania - Chereches, Ioan Aurel; Arion, Iulia Diana; Muresan, Iulia C.; Gaspar, Ferenc (Sustainability, 2023)
Many concerns are arising now regarding the effects of the pollution on inhabitants, especially in agglomerated areas. It is known that mobility is a major factor that generates threatening pollution that negatively affects the health and the comfort of residents. The present study focuses on this sensitive subject by observing the impact of reducing mobility on air quality. There are various studies on this topic, but this analysis addresses a gap in the literature, by covering a very active area, in terms of development and attractiveness for new inhabitants. The research study was carried on Cluj-Napoca city (Romania), by measuring the concentration of SO2, NO2, O3, PM10, PM2.5 from five different air monitoring stations from Cluj County during 2019–2021. During the entire period, the concentrations of the measured pollutants regarding the air quality were far below the legally accepted limits, with some short time peaks generated by other human factors. Road vehicle traffic generates pollution, but they are not the only elements that have to be taken into consideration when the quality of life is regarded, so the lawmakers have a more complex task to comply when deliberating on this matter. It concludes that it is necessary to develop on the existing air quality measuring network stations, because it is necessary to increase the number and the quality of the measurements.